2022
DOI: 10.1212/wnl.0000000000200709
|View full text |Cite
|
Sign up to set email alerts
|

Incident Herpes Zoster and Risk of Dementia

Abstract: Background and Objectives:Herpes zoster is caused by reactivation of the neurotrophic varicella-zoster virus. Zoster may contribute to development of dementia through neuroinflammation, cerebral vasculopathy, or direct neural damage, but epidemiological evidence is limited. We used data from linked nationwide Danish registries to conduct a cohort study of the association between zoster and dementia during 1997 to 2017. As secondary aims, we examined if associations were more pronounced for zoster involving cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 53 publications
1
16
2
Order By: Relevance
“…17,18 Herpesvirus infections have gained the most attention but with mixed results, and all recent large studies except one showed no increased dementia risk. [19][20][21][22][23][24] In our study, for any herpesvirus infection, only short-term estimates were significant.…”
Section: Infectionscontrasting
confidence: 67%
See 1 more Smart Citation
“…17,18 Herpesvirus infections have gained the most attention but with mixed results, and all recent large studies except one showed no increased dementia risk. [19][20][21][22][23][24] In our study, for any herpesvirus infection, only short-term estimates were significant.…”
Section: Infectionscontrasting
confidence: 67%
“…Other previous studies investigated specific infections and reported increased dementia risks associated with gastrointestinal infections, sepsis, and pneumonia . Herpesvirus infections have gained the most attention but with mixed results, and all recent large studies except one showed no increased dementia risk . In our study, for any herpesvirus infection, only short-term estimates were significant.…”
Section: Discussioncontrasting
confidence: 56%
“…Moreover, Schmidt et al [55] revealed that dementia risk was nearly doubled in the first year following cranial nerve HZ (HR 1.83; 95%CI = 1.03-3.25), with the ophthalmic nerve accounting for the majority of cases (83%; 990 of 1190). These findings are consistent with ours and those of Tsai et al [36] According to Schmidt et al, [55] neuroinflammation and direct cerebral injury may act as a potential mediators in the association between HZ affecting the CNS and dementia. Even though vasculopathy may be implicated, integrating stroke diagnosis into the mediation model failed to lower HRs.…”
Section: Discussionmentioning
confidence: 99%
“…In a revival of the viral hypothesis of AD [101], the possible implication of certain viral infections in ADRD risk is receiving increasing attention, particularly the reactivation of latent neurotropic viruses of the Herpesviridae family, including herpes simplex virus 1 and 2 (HSV-1/2), varicella-zoster virus (VZV), and Epstein-Barr virus (EBV). Indeed, numerous epidemiological studies in the last few years have tried to address this question but yielded conflicting results (Table 2) [8,22,45,53,66,71,79,97,98,105,111]. Reasons for these mixed findings are likely methodological, including differences in study design (population-based longitudinal cohort vs. electronic health records or claims data), ascertainment of viral exposure (positive IgM or IgG serology vs. ICD codes and/or medical records of antiviral treatment) and of dementia and/or AD diagnosis (ICD codes vs. expert diagnosis), and length of follow-up (a shorter follow-up is prone to reporting bias, thus overestimating the link between viral infection and dementia).…”
Section: Epidemiological Evidencementioning
confidence: 99%